PRODUCTIVITY OF MANGOLD VARIETY SAMPLES IN UZBEKISTAN (Modern American Journal of Biological and Environmental Sciences, 2025)
In the soil and climatic conditions of Uzbekistan, among the mangold variety samples, the highest leaf yield was observed in the Raduga (35.3 t/ha), Brazilskiy (34.4 t/ha), and Krasavitsa (33.7 t/ha) varieties, while the lowest leaf yield was observed in the Rubin (22.3 t/ha), Aliy (22.3 t/ha), Zeleniy (21.1 t/ha), and Lukullus (14.5 t/ha) varieties.